Proteolytic Regulation of the Lectin-Like Oxidized Lipoprotein Receptor LOX-1 - Mentrup, Torben; Cabrera-Cabrera, Florencia; Schröder, Bernd (Frontiers in Cardiovascular Medicine, 2021)
The lectin-like oxidised-LDL (oxLDL) receptor LOX-1, which is broadly expressed in vascular cells, represents a key mediator of endothelial activation and dysfunction in atherosclerotic plaque development. Being a member of the C-type lectin receptor family, LOX-1 can bind different ligands, with oxLDL being the best characterised. LOX-1 mediates oxLDL uptake into vascular cells and by this means can promote foam cell formation. In addition, LOX-1 triggers multiple signalling pathways, which ultimately induce a pro-atherogenic and pro-fibrotic transcriptional program. However, the molecular mechanisms underlying this signal transduction remain incompletely understood. In this regard, proteolysis has recently emerged as a regulatory mechanism of LOX-1 function. Different proteolytic cleavages within the LOX-1 protein can initiate its turnover and control the cellular levels of this receptor. Thereby, cleavage products with individual biological functions and/or medical significance are produced. Ectodomain shedding leads to the release of a soluble form of the receptor (sLOX1) which has been suggested to have diagnostic potential as a biomarker. Removal of the ectodomain leaves behind a membrane-bound N-terminal fragment (NTF), which despite being devoid of the ligand-binding domain is actively involved in signal transduction. Degradation of this LOX-1 NTF, which represents an athero-protective mechanism, critically depends on the aspartyl intramembrane proteases Signal peptide peptidase-like 2a and b (SPPL2a/b). Here, we present an overview of the biology of LOX-1 focusing on how proteolytic cleavages directly modulate the function of this receptor and, what kind of pathophysiological implications this has in cardiovascular disease.